Omental Metastasis of Malignant Phyllodes Tumor: A Case Report - Bhambhani, Navin; Gori, Jayesh; Pramesh, CS; Kulkarni, Chandrashekar; Nambiar, Ajit; Badwe, RA (International Journal of Medical Research and Review, 2015)
Malignant Phyllodes tumor behaves like sarcomas and has a tendency for local spread and for local recurrence. The metastasis commonly known is blood borne and is usually to the lungs, mediastinum and skeleton rather than to the axillary lymph nodes. In present case of malignant phyllodes tumor there was metastasis to omentum, probably the only reported case in English literature.